Principal decision-making in implementing Merdeka Curriculum in elementary schools: a review - Wijayanti, Dian Marta; Pramono, Suwito Eko; Handoyo, Eko (International Journal of Evaluation and Research in Education (IJERE), 2024)
This research uses a literature review that examines current articles on principals’ decision-making in implementing the Merdeka Curriculum in elementary schools. The literature review method is assisted by Open Knowledge Maps (OKM) and literature searches using Google Scholar, ERIC, ScienceDirect, and PubMed databases. The findings of this research suggest that principals’ decision-making in curriculum implementation has a significant impact on the quality of education in schools. By considering these aspects, principals can ensure that the curriculum implemented in their schools meets the needs of students and contributes to the achievement of broader educational goals. Principals’ decision-making in implementing the Merdeka Curriculum requires a deep understanding of education, leadership skills, and the ability to collaborate. The implementation of the Merdeka Curriculum is a significant change in Indonesia’s education system that aims to tailor education to local needs better, develop students’ character, and promote competency-based learning. However, successful implementation requires adequate support, training, and resources for schools and educators. This research is limited to a literature review only. So, in the future, it is necessary to carry out field research in order to reveal the principal’s decision-making in implementing the Merdeka Curriculum with various new methods and adapted to current issues.